A Review: Robust Locomotion for Biped Humanoid Robots. (March 2020) - Xie, Ye; Lou, Bin; Xie, Anhuan; Zhang, Dan
Abstract: One of the most interesting and pressing challenges in the study on biped humanoid robots is to achieve high robustness in locomotion. This paper presents a brief overview of work and methods on robust walking and running for bipedal robots. So far, many robust walking methods have been proposed to reject terrain disturbances and impulsive force disturbances. The applications of the proposed methods to real robots improve the robustness and adaptivity of robots by large margin. Up to now, bipedal robots can traverse unknown terrains with ground variation exceeding 20% of leg length. The height of obstacles increases more than threefold compared to decades ago. With regards to unexpected external force, bipedal robots can recover the balance from sudden push not only at stationary state, but also during the walk. On the other hand, the biped running is underdeveloped compared to the robust walking. Still the highest running speed is less than 3.0 m/s, not to mention the poor robustness to large disturbances.